Islamic Banking Education in Maqasid Al-Mu'amalat’s Perspective - Oktaria Ardika Putri; Muhammad Solikhudin (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
Abstract: This article explains the role of tertiary education in Islamic banking in Indonesia with a review of maqa>sid al-mu'a>mala>t. As known, the development of Islamic banking is still being pursued today. Accordingly, the public's need for an understanding of Islamic banking and the need for experts in the field of Islamic banking cannot be denied. Therefore, it requires experts who have graduated from the Islamic banking study program from universities, including the Kediri State Islamic Institute, to answer this challenge. The contribution of higher education in the Islamic banking study program to produce excellent graduates is an important thing that must be realized. Islamic banking education, when viewed by maqa>sid al-mu'a>mala>t, it is known that real certainty is manifested, such as a comprehensive understanding of Islamic banking in terms of compliance with Islamic banking principles which includes compliance with the principles of Islamic banking. Sharia principles, prudential provisions, increased operational efficiency which will have an impact on high competitiveness and stability of the Islamic banking system as well as benefits to the economy. There is also a universal dimension, namely the general benefit between the government, Islamic financial institutions and the public. Keywords: Education, Islamic Bank, Maqa>sid al-Mu'a>mala>t. Abstrak: Artikel ini menerangkan peran pendidikan perguruan tinggi dalam perbankan syariah di Indonesia dengan tinjaun maqa>sid al-mu’a>mala>t. Seperti diketahui, pengembangan perbankan syariah masih diupayakan sampai saat ini. Sesuai dengan itu, kebutuhan masyarakat terhadap pemahaman perbankan syariah serta kebutuhan tenaga ahli di bidang perbankan syariah tidak dapat dipungkiri. Oleh sebab itu, butuh tenaga ahli lulusan program studi perbankan syariah dari perguruan tinggi, termasuk Institut Agama Islam Negeri Kediri, untuk menjawab tantangan ini. Kontribusi pendidikan tinggi program studi perbankan syariah untuk melahirkan sarjana-sarjana yang unggul, merupakan hal penting yang harus direalisasikan. Pendidikan perbankan syariah, apabila ditinjau dengan maqa>sid al-mu’a>mala>t, maka diketahui, terwujud kepastian yang nyata, seperti pemahaman yang menyeluruh tentang perbankan syariah dalam hal kepatuhan pada prinsip perbankan syariah yang meliputi kepatuhan pada prinsip-prinsip syariah, ketentuan kehati-hatian, peningkatan efisiensi operasional yang berdampak pada daya saing yang tinggi dan stabilitas sistem perbankan syariah serta kemanfaatan bagi perekonomian. Terwujud juga dimensi universal, yakni kemaslahatan umum antara pemerintah, lembaga keuangan syariah dan masyarakat. Kata Kunci: Pendidikan, Bank Syariah, Maqa>sid al-Mu’a>mala>t.